PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TERPADU BERBASIS INQUIRY MELALUI LESSON STUDY (Universitas Ivet, 2015)
The research aims is to develop an integrated science learning instruments based inquiry by lesson study that can improve students interest and creativity, knowing effectivity and practically of integrated science learning instruments based inquiry by lesson study. This development of learning instruments is done by lesson study using research and development model by Plomp in 5 phase, namely (1) preliminary investigation, (2) design, (3) realization/construction, (4) test, evaluation, and revision, and (5) implementation. Implement of the research in SMP N 6 Semarang class VII semester 2. Instruments and technique of collect data is used by checklist, observation, questionnaire, and test method. Analysis data to know the instruments of this research is valid, effective, and practical with count of valid instruments of the data, carried out learning, students interest, students creativity, students response, data of result study, gain of students interest and creativity, and significance test. Result validation of syllabus, lesson plan, and learning material based inquiry wich develop by lesson study indicate: (1) learning instruments are valid, practical, and effective, (2) students interest and creativity increase, (3) more than 80% students have given good responses, (3) classical completeness learning is more than 75%. Thus, we can conclude that development of integrated science learning instruments based inquiry by lesson study are effective and practical to improve students interest and creativity, so the result study can optimal. This research needs to be continuous to solve the problems on learning and get a quality of learning.Â Key words : integrated science learning instruments, inquiry, and lesson study